The Role of ESG, Fundamental Factors, and Market Perception on Financial Performance: Evidence from LQ45 Firms in Indonesia - Bilqis Saffana Zahrazova; Kiki Nita; Moh. Yudi Mahadianto; Mada Purwanto Wahyu Nugroho (Rescollacom (Research Collaborations Community), 2025)
This research is conducted with the objective of empirically analyzing how sustainability elements and core corporate characteristics influence the financial performance of issuers listed on the LQ45 index at the Indonesia Stock Exchange between 2019 and 2023. The focus of the investigation lies in exploring the impact of Environmental, Social, and Governance (ESG) scores, capital structure metrics, Earnings per Share (EPS), firm scale, and market-based valuation indicators on profitability, measured through Return on Assets (ROA) and Return on Equity (ROE). Adopting a quantitative research approach, this study applies panel data regression techniques. The sample selection process utilizes purposive sampling, emphasizing the availability of complete annual reports, sustainability disclosures, and ESG ratings obtained from Sustainalytics. From a total of 225 observations, 169 datasets met the stringent criteria for thorough examination. The results highlight that prudent management of capital structure combined with strong market valuation significantly boosts corporate profitability. Conversely, the incorporation of ESG practices does not uniformly translate into immediate financial gains and, in certain cases, may even detract from profitability levels. Additionally, the analysis indicates that firms with larger asset bases may experience a decline in operational efficiency, suggesting that mere expansion in size does not inherently enhance financial outcomes. These findings provide valuable insights into the expanding body of literature addressing environmental, social, and governance (ESG) and corporate financial performance within emerging market environments. Furthermore, they offer practical recommendations for regulators, corporate leaders, and investors aiming to design more integrated, sustainability-oriented financial strategies.